Lysosome‐Related Effector Vesicles in T Lymphocytes and NK Cells. (September 2015) - Lettau, M.; Kabelitz, D.; Janssen, O.
Abstract Lysosome‐related secretory organelles combine metabolic functions of conventional lysosomes with an inducible secretory potential. Specialized variants of such bi‐functional organelles are present in several haematopoietic cell types that store, mobilize and/or secrete effector proteins, for example in mast cells, macrophages or cytotoxic effector cells. In the case of T lymphocytes and NK cells, it was believed that secretory lysosomes serve as a common storage and transport compartment for the most relevant cytotoxic effector proteins including FasL, perforin, granzymes and granulysin. However, recent observations suggest that cytotoxic effector cells might be able to mobilize two distinct lysosomal entities in order to react to differential stimulation with either FasL surface appearance or degranulation‐associated release of perforin and granzymes. This assumption is supported by the proteomic characterization of enriched organelles from T and NK cells. FasL‐associated light lysosomes biochemically segregate from morphologically distinct heavy lysosomes that preferentially contain granzymes, perforin and mature granulysin. Here, we briefly summarize the current knowledge about cargo proteins that are stored and transported in secretory vesicles and how these vesicles might be generated and mobilized. In addition, we describe common features and major differences of the two distinct effector organelles and discuss how these observations might expand existing models of cytotoxic effector function.